Edukasi Tentang Pentingnya Pendidikan Hukum Bagi Pelajar SMK Negeri 1 Kaidipang - Djaafar, Lucyane; Mozin, Nopiana; Mbuinga, Yudha (Civic Education Law and Humaniora : Jurnal Pengabdian Masyarakat Terintegrasi, 2023)
The family is an effective legal socialization place before a child directly becomes a member of society. Parents become a very important figure in providing examples of law enforcement in Indonesia. Then from the family environment will continue to the school environment and the outside community in general. When a child has started to grow into an adult, then at that time a new individual begins to be introduced to the rules and principles of state law which they know through the legal education they receive both formally and informally. Understanding of the law can be done with legal counseling. Legal counseling means a conscious effort made by someone to comply with applicable legal rules. The methods of implementation are Activity Stages, Preparation and Debriefing Materials, and Program Action Plans. The results of the collaborative community service activities for lecturers and students in the form of socialization are as follows (1) Increased legal awareness of students at SMKN 1 Kaidipang. (2) The behavior of students at SMKN 1 Kaidipang who obeys the law is formed. (3) The characteristics of students at SMKN 1 Kaidipang who understand the law grow. With legal awareness within the students of SMKN 1 Kaidipang, they will easily realize that it is important to comply with existing regulations so that they can apply them and become an example for young and old people in their area, so that they will get used to complying with regulations and carrying out law well wherever they are.